Interação Natural por Meio de Gestos para Apoio a Docentes no Processo de Ensino em Saúde - Ferreira, Douglas dos Santos (2014)
In the field of human-computer interaction, Natural Interaction methods has been gaining importance because they provide communication between user and machine through an easy and intuitive way, by interpreting the natural actions of persons. Optical tracking devices are important in this context, because it provides the tracking of human body, obtaining information that can be used to provide the interaction by a natural way. In the development of Virtual Reality systems for health, there is a need to produce forms of interaction that are similar to the commonly performed by people in daily activities. Because of its intuitive features, the Natural Interaction can perform an important role in this scenario, benefiting the process of human-computer communication. It is important to emphasize that some natural behaviors can be of cultural origin, creating the need to identify specific features target audience for an interaction with applications that provide natural interfaces. The general goal of this work is to discuss a set of techniques for Natural Interaction by gestures for use in tracking systems by optical devices to support professors in health teaching activities. It is also presents the development and validation of a Natural Interaction module for a framework for developing Virtual Reality systems for health.